Anthelmintic effectiveness of modern preparations against Heterakis gallinarum nematodes parasitizing in chickens - Omelchenko, O. (Scientific Progress & Innovations, 2024)
In poultry farming, heterakosis is one of the most widespread parasitic diseases and causes significant damage to the industry. At present, for chemoprophylaxis and treatment of poultry for this infestation, manufacturers have offered a sufficient number of preparations that have nematocide effect. At the same time, the effectiveness of anthelmintic preparations available on the domestic market has not always been studied and highlighted in scientific papers. The purpose of the research was to study the effectiveness of preparations with different active substances and different methods of application for spontaneous chicken heterakosis. Anthelmintics in the form of powder – Levamisole 80 (the active substance is levamisole hydrochloride) and Albendazole Ultra 10 % (the active substance is albendazole), as well as in the form of the solution and suspension with the analogous active substances – Levamisole-plus 10 % and Albendazole 10 %, were tested. A high effectiveness of Levamisole-plus 10 % for chicken heterakosis was established by the conducted studies, where on the 14th day of the experiment, the extense- and intenseeffectiveness reached 100 %. The efficacy indicators of this preparation on the 3rd day were 70 and 95.44 %, respectively, and on the 7th day they already reached 100 %. Albendazole suspension and Levamisole 80 turned out to be moderately effective. The indicators of extense- and intenseeffectiveness on the 14th day of treatment with Albendazole suspension were 80 and 95.67 %, and with Levamisole 80 – 80 and 78.78 %. During the experiment, the effectiveness of Albendazole suspension gradually increased and was 60 and 91.63 % on the 3rd day and 80 and 96.57 % on the 7th day, respectively. When applying Levamisole 80 to the diseased poultry, the indicators of extenseeffectiveness increased from the 3rd to the 7th day from 30 to 80 %, and intense-effectiveness decreased from 83.77 to 81.13 %. Albendazole Ultra10 % preparation turned out to be insufficiently effective: its indicators of extense- and intenseeffectiveness on the 14th day of the experiment made 60 and 73.93 %, respectively. During the experiment, the efficacy indicators of Albendazole Ultra 10% gradually increased from the 3rd to the 7th day – from 20 to 80 % and from 76.45 to 76.71 %. On the 14th day, the indicators of extenseeffectiveness remained at the same level, and those of intenseeffectiveness decreased. The obtained results of experimental studies allow recommend Levamisole-plus 10 % anthelmintic preparation for effective control and prevention of chicken heterakosis.